Congenital absence of the intrahepatic segment of the inferior vena cava with azygos continuation presenting as a mediastinal mass. Issue 762 (April 1989) - Beedie, R. J.; Yeo, W.; Morcos, S. K.
Abstract : A child with the isolated anomaly of azygos continuation of the inferior vena cava is presented. The interest of this abnormality lies in its detection as a mediastinal mass on the chest radiograph. Computed tomography with intravenous contrast enhancement is the method of choice to diagnose this venous anomaly. Awareness of the caval-azygos abnormality is important to surgeons and cardiologists. Accidental ligation of the azygos vein is fatal and cardiac catheterization using the lower extremity vein is troublesome in patients with this condition.